Über die Stetigkeit des Operators Fx(t) = F(t, x(t)) in normierten Produkträumen - Mänz, P. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: П. Менц. О непрерывности оператора суперпозиции, действующего в нормированных произведениях пространств P. Mencas. Apie superpozicijos operatoriaus, veikiančio normuotų erdvių sandaugose, tolydinumą